What do Secular-believer Women in Israel Believe in? - Lahav, Hagar (Journal of contemporary religion, 2016)
Secular-believers, who constitute about 25% of Israeli Jews, are self-identified secular people who believe in some kind of divinity. Based on in-depth interviews with secular-believer women, this study aims to reveal their theological assumptions and claims. It examines metaphors and images participants used to relate to the divine as well as the theological categories they emphasized. The study uncovers the pluralistic nature of secular-believers' beliefs and the common tendency to address faith-related content in a positive light.